Traditional Chinese Medicine nursing of a patient with late-stage acute lactational mastitis (1例哺乳期急性乳腺炎溃后期患者的中医护理) - ZHANG Furong (张芙蓉); LIU Jing (刘静); GAO Jingshan (高婧珊); FAN Yingyi (樊英怡); LIU Shuan (刘栓); TANG Ling (唐玲) (中西医结合护理)
This paper summarized the treatment and nursing experience of a patient with late-stage acute lactational mastitis. Nursing measures included Traditional Chinese Medicine external application, nursing evaluation, massage for milk lactation, dressing change, health education. After intervention, patient had resumed breastfeeding and wound was well-healed, representing the characteristic of disease prevention in Traditional Chinese Medicine. (本文总结1例哺乳期患者急性乳腺炎溃后期的治疗和护理经验。护理措施包括中药贴敷、护理评估、手法排乳、换药、健康宣教等。干预后, 患者恢复母乳喂养, 创面愈合, 充分体现了中医“未病先防, 已病防变”的特色。)